A new perspective on scoring children’s originality: a standards-based criterion-referenced assessment approach - Kadir Bahar; Carol June Maker (Frontiers in Psychology)
In this paper, we proposed and discussed the use of a standards-based criterion-referenced assessment (CRA) approach in scoring originality with a specific focus on teaching for creativity. Throughout the paper, we supported our perspective with examples, particularly addressing evidence-based educational models that were designed to develop students’ ability to solve real problems in creative and effective ways in different domains. Given the importance of using proper assessment methods in fostering and monitoring learning, we believe such an approach might have significant implications for teaching practices and future research.